NextGeners: Pedagogical Considerations - Griffith, Bryant (BRILL, 2016)
NextGeners bring vibrant life experiences, risk taking, and creativity into the classroom. They demand to be included in the 'why' and 'how' of learning. Teachers bring a love of learning, empathy, content and theoretical perspective that serves as a setting for how the classroom should operate. The author argues that NextGeners understand personalized viewpoints but often miss that teaching and learning are grounded in a process of historical interactions. Second, NextGeners are social beings living in and defined by social media and the web. We must invite both to share how to construct shared understanding and build a learning community that makes sense in our emerging paradigm.